Projects: Expanding Horizons (2013)
Over the past few years, the Children's University team has wondered: how can the program transcend EAFIT's borders? A question that arises from two intentions: to offer new audiences the methodology developed and to generate alliances with other organizations working to improve the education and communication of science.